FORM OF PRESENTATION WORSHIP SONG AT HKKBP SUTOYO - Simanjuntak, Clarissa Tessalonika; Nur Saputra, Dani; Joko Srimoko, Gandung (Program Studi Pendidikan Musik, 2023)
The purpose of this research is to describe the form of worship music reviewed in the arrangement that is present at HKBP Sutoyo Church. The research method used is qualitative with a descriptive approach. The results showed that the form of worship music at HKBP Sutoyo Church was mixed music in a band format using electric pianos, keyboards, electric guitars, electric basses, electric drums, and singing guides. Form of presentation in arrangement of worship music has variations in the processing of melodies in the musical accompaniment, processing of singing forms, use of chords and various progressions, use of sound effects, variations of beats and musical genres which can provide a different atmosphere in each worship song.